Plogging: an environmentally friendly fitness trend, a sustainable initiative / Nur Idzhainee Hashim - Hashim, Nur Idzhainee (UiTM Cawangan Negeri Sembilan, 2023)
Plogging is a new sustainable movement that mixes sports like jogging with environmental awareness. The act of picking up rubbish and litter while jogging is known as plogging. Picking up litter on jogs, runs, treks, walks, and bike rides is something that plogging can accomplish. Plogging is a way to get some exercise while also keeping the region clean by picking up trash. It's a simple exercise that anyone may participate in. We can practice plogging while exercising because its benefits Mother Nature as well as our bodies, minds, and spirits. Plogging is an environment friendly trash workout is a combination of jogging with litter collection. The first plogging in Malaysia began in Taman Tasik Titiwangsa, Kuala Lumpur. As a result, plogging is not new in our country and is growing in popularity among Malaysians. This is due to the fact that plogging has become popular and has spread to other nations, including Malaysia. When plogging, gloves and plastic bags are optional but advised. Plogging has several advantages, including being healthy for the heart, raising self-esteem, reducing weight, improving performance, and strengthening bones.